Pārati iyal - Caṇmukam, Irāma (Maturai Kāmarācar Palkalaik Kaḻaka Añcalvaḻit Toṭarkalvit Tamiḻt Tuṟai veḷiyīṭu, 1982)
Papers, presented at the Bharati Centennial Seminar, Madurai Kamaraj University, on the life and works of Paratiyar, 1882-1921, Tamil litterateur and Indian freedom fighter.